(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Hypothyroidism is associated with many biochemical abnormalities including increased serum alanine aminotransferase activity. Very few studies have been done regarding serum alanine aminotransferase activity in hypothyroid patients and, as far we know, no such study has been done in our populations. So, we designed this study in our population for evaluation of serum alanine aminotransferase activity in hypothyroid patients. The objective of this study was to assess serum alanine aminotransferase activity in hypothyroid patients and to find out relationship of alanine aminotransferase activity with severity of hypothyroidism. Methods: It was a retrospective cross sectional study to evaluate the serum alanine aminotransferase activity of hypothyroid patients and to find out relationship of alanine aminotransferase activity with severity of hypothyroidism and the values were compared with that of age and sex matched healthy euthyroid controls. Statistical analyses were performed by using SPSS for Windows version 12.0. Unpaired t test was done to find out any significant difference between the cases and controls with respect to age and serum alanine aminotransferase activity. Chisquare test was done to find out any significant difference between the cases and controls with respect to sex. Pearson correlation coefficient test was done to see the correlation of alanine aminotransferase activity with the severity of hypothyroidism. Results: Mean serum alanine aminotransferase activity was found significantly higher in hypothyroid patients compared to that of controls. Conclusion: Results of our study suggest that increased serum alanine aminotransferase activity is associated with hypothyroidism. Therefore, patients presenting with increased ALT activity with normal liver function tests are recommended to be investigated to explore hypothyroidism. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 49-51